2007
DOI: 10.1007/s10822-007-9126-y
|View full text |Cite
|
Sign up to set email alerts
|

Outliers in SAR and QSAR: 2. Is a flexible binding site a possible source of outliers?

Abstract: Structure-activity relationship (SAR) and/or quantitative structure-activity relationship (QSAR) studies play an important role in a lead optimization of drug discovery research. When there is a lack of ligand-bound protein structural information, one of the assumptions in SAR and QSAR studies is that similar analogs bind to the same binding site in a similar binding mode. In such studies, outliers have often been observed, especially in QSAR. However, most of these studies have focused their attention on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This collection has provided not only access to models for novel applications, but allows the analysis of QSAR models to identify challenges for the field. Kim (2007) examined the C-QSAR data base for outlier patterns, i.e., compounds that showed poor prediction when the average prediction for the model was good. They found that of over 47 QSAR models examined, the number of compounds scoring as outliers ranged from 3 to 36%.…”
Section: Quantitative Structure-activity Relationship Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This collection has provided not only access to models for novel applications, but allows the analysis of QSAR models to identify challenges for the field. Kim (2007) examined the C-QSAR data base for outlier patterns, i.e., compounds that showed poor prediction when the average prediction for the model was good. They found that of over 47 QSAR models examined, the number of compounds scoring as outliers ranged from 3 to 36%.…”
Section: Quantitative Structure-activity Relationship Modelsmentioning
confidence: 99%
“…They found that of over 47 QSAR models examined, the number of compounds scoring as outliers ranged from 3 to 36%. Twenty-six of the 47 datasets showed 20% or more compound outliers (Kim, 2007). They presented several theories as to why QSAR models are so sensitive to the generation of outliers.…”
Section: Quantitative Structure-activity Relationship Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,70,89 In cases where the ligand binding mode is maintained as functional groups are modified, conventional relative free energy calculations may often work well without any special treatment of alternate potential binding modes. However, small modifications to ligands do on occasion yield big differences in ligand binding orientation, 65,88,[90][91][92][93][94][95][96][97] and there is currently no way to know when this will happen. For example, Stout et al developed a series of thymidylate synthase (TS) inhibitors based on phenolphthalein and phthalein derivatives.…”
Section: E Binding Modes Are Difficult To Predictmentioning
confidence: 99%
“…There may be a lack of certain descriptors or parameters to describe QSAR for entire compounds. A different mechanism mode may even be a reason (21). Table 3.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%